Gene expression profiles in testis of developing male Xenopus laevis damaged by chronic exposure of atrazine. (September 2016) - Sai, Linlin; Dong, Zhihua; Li, Ling; Guo, Qiming; Jia, Qiang; Xie, Lin; Bo, Cunxiang; Liu, Yanzhong; Qu, Binpeng; Li, Xiangxin; Shao, Hua; Ng, Jack C.; et al.
Abstract: As a widely used herbicide, atrazine (AZ) has been extensively studied for its adverse effects on the reproductive system, especially feminization in male animals. However, the relationship of gene expression changes and associated toxicological endpoints remains unclear. In this study, developing Xenopus laevis tadpoles were exposed to concentration of AZ at 0.1, 1, 10 or 100 μg/L continuously. Compared with froglets in the control group, there were no significant differences in body length, body weight, liver weight and hepatosomatic index (HSI) of males in groups treated with AZ for 90 d. At 100 μg/L AZ treatment caused a significant reduction of gonad weight and gonadosomatic index (GSI) of males ( p < 0.01). In addition, AZ at all dose levels caused testicular degeneration, especially in froglets from the groups with 0.1 and 100 μg/L which exhibited U-shaped dose-response trend. We further investigated the gene expression changes associated with the testicular degeneration induced by AZ. We found that the expression of 1165 genes was significantly altered with 616 upregulated and 549 downregulated compared to the expression profile of the control animals. KEGG analysis showed that genes which were significantly affected by AZ are mainly involved in arginine and proline metabolism, cell cycle, riboflavin metabolism, spliceosome, base excision repair and progesterone-mediated oocyte maturation pathway. Our results show that AZ may affect reproductive and immune systems by interference with the related gene expression changes during the male X. laevis development. The findings may help to clarify the feminization mechanisms of AZ in male X. laevis . Highlights: AZ at 0.1 and 100 μg/L caused testicular degeneration in Xenopus laevis . 100 μg/L AZ upregulated 616 and downregulated 549 genes. AZ altered genes expression related to reproductive and immune systems. Six pathways were significantly affected after chronic AZ exposure.